Assessing the diet and trophic niche breadth of an omnivorous fish (Glanidium ribeiroi) in subtropical lotic environments: Intraspecific and ontogenic responses to spatial variations - Kliemann, B. C.K. [UNESP]; Baldasso, M. C.; Pini, S. F.R.; Makrakis, M. C.; Makrakis, S.; Delariva, R. L. (CSIRO Publishing, 2019)
The diet of Glanidium ribeiroi was investigated in lotic stretches downstream from a cascade of reservoirs to determine how it responds to intraspecific and environmental variations. Monthly sampling was performed from 2013 to 2016 at sites including the main channel of the Iguaçu River and tributaries in preserved basins and agricultural land. The diet of individuals in the preserved tributaries was primarily associated with allochthonous resources, whereas in the non-preserved tributaries and main channel the diets were primarily associated with autochthonous resources. Trophic niche breadth and intraspecific variability differed significantly among sampling areas and size classes. Trophic niche overlap among size classes and sampling areas was low. Positive and negative relationships between the trophic niche breadth and the standard length of individuals were also found in different sampling areas. Intraspecific and ontogenic variations were strongly and consistently associated with forest cover. Individuals responded differently to local environmental variations due to differences in landscape gradients and life cycle changes. Therefore, the effects of spatial heterogeneity on diet composition and intraspecific variations therein appear to be crucial to the success of the populations evaluated. These results may help with the implementation of conservation measures for this and other endemic species.
Keywords: allochthonous resources; feeding; fish freshwater; preserved areas; trophic segregation